Japanomania in the Nordic countries 1875-1918 - Bonsdorff, Anna-Maria von; Selkokari, Hanne; Weisberg, Gapriel P. (Ateneum publications, 2016)
This extensive publication, complete with hundreds of illustrations by such renowned artists as Carl Larsson, Edvard Munch, Vilhelm Hammershoi, Pekka Halonen, Akseli Gallen-Kallela, Christopher Dresser, Pietro Krohn, Alf Wallander, and Frida Hansen, among others, offers an unprecedented study of Japanese influence on the visual arts in the Nordic countries. This unlikely diffusion of Japanese culture, known collectively as Japonisme, became increasingly apparent in England, France, and elsewhere in Europe during the 19th century, although nowhere was the influence seemingly as pervasive as it was throughout the Nordic countries. The book reveals how the widespread interest in Japanese aesthetics helped to establish notions of a fundamental unity between the arts and transformed the region's visual vocabulary. The adoption of Japanese motifs and styles in Finland, Norway, Sweden, and Denmark provided a necessary cohesion to their existing artistic language, forming a vital balance within and among all of the applied arts. 0Exhibition: Ateneum Art Museum, Helsinki, Finland (17.02-15.05.2016) / National Gallery of Norway, Oslo, Norway (16.06-16.10.2016) / National Gallery of Denmark, Copenhagen, Denmark (19.01-21.04.2017).
Keywords: 1800-luku; 1900-luku; 1800-talet; 1900-talet; Arts; Visual arts; taide; taiteenlajit; japonismi; konst; konstarter; japonism; Pohjoismaat; Norden; visuaalinen taide